Qualidade de sobrecoxas de frangos submetidas à radiação UV-C - Dugatto, Jonas Simon (2012)
During the chicken slaughter line, some steps are considered critical, due to the possibility of cross-contamination among carcasses, which directly influence in the shelf-life of the carcasses. New technologies that reduce the microbial counts, leading to an increase of the quality and shelf-life are very welcome. The ultraviolet-C (UV-C) radiation appears as an alternative, because is a non-thermal method, of low cost and of easy implementation, which has already proved to be lethal to many microorganisms in food surfaces. Thus, this work aimed to evaluate the use of doses of UV-C radiation of 5,4 and 9,46 kJ/m2, applied at two temperatures near the slaughter steps (5 and 25 °C), on the physicochemical parameters (color, pH, conjugated dienes content, peroxide value, thiobarbituric acid reactive substances and fatty acid profile) and microbiological (total aerobic mesophilic bacteria, psychrotrophic, yeasts and molds) of chicken drumsticks. The analyses were performed immediately after the doses were applied (zero day) and every 3 days, during 12 days of storage at 5 °C, but the fatty acid profile was analyzed after the doses were applied, and on sixth and twelfth days. The number of colonies of total aerobic mesophilic bacteria had significant reductions (p < 0,05) on the third, sixth and ninth days of storage, at both temperatures of application and after the doses were applied (zero day) for the application at 25 °C. Regarding the total aerobic mesophilic bacteria, application of UV-C radiation at 5 °C, provided shelf-life of carcasses of 9 days of storage, whereas at 25 °C, the shelf-life was 6 days. The number of colonies of psychrotrophic bacteria had significant decreases (p < 0,05) in all days of storage when applied the dose of 9,46 kJ/m2 at 5 °C, and only on the third and on the twelfth days when applied at 25 °C. At the sixth day, the number of colonies of psychrotrophic bacteria was characteristic of deterioration, regardless the treatment applied. The molds and yeasts were not affected by UV-C radiation. Generally, in a same temperature of application, the UV-C radiation doses didn t cause significant changes (p > 0,05) compared to the samples from the control group (without irradiation) in any of the physicochemical parameters, independent of the day of storage. The application of UV-C radiation at 25 °C compared to 5 °C, promoted higher formation of conjugated dienes and lower amount of omega-6 and omega-3 polyunsaturated fatty acids. Thus, the UV-C radiation could be applied in industry after the step of cooling carcass (at 5 °C) due to the non-acceleration of initiation of lipid oxidation, the non-diminishing of essential fatty acids and being effective on the reduction of aerobic mesophilic and psychrotrophic bacteria.